Clinical, laboratory, and virological characteristics of patients with positive hepatitis B surface antigen in Upper Egypt - Khairy H Morsy; Mohamed AA Ghaliony; Tarek T.H. El Melegy (SpringerOpen, 2015)
Aim The aim of the study was to determine the clinical, laboratory, and virological characteristics of patients with chronic HBV infection in Upper Egypt. Patients and methods This descriptive, cross-sectional study included 252 patients with positive hepatitis B surface antigen (HBsAg). It was conducted in the Tropical Medicine and Gastroenterology Department and Outpatient Clinic, Assiut University Hospital (Egypt), from May 2012 to May 2014. All patients underwent clinical evaluation, were administered a questionnaire about risk factors for transmission of HBV, underwent liver function tests, abdominal ultrasonographic examination, and complete blood count, evaluation of serological markers of HBV, and quantitative detection of HBV-DNA. Results Of the 252 patients included, 88.5% were male with a mean age of 35.4 years. Arthralgia was the most common complaint (15.5%) and hepatomegaly was the most common finding (8.3%). As regards imaging Results (ultrasonographic) the following were found: normal liver in 83.3%, coarse liver in 11.9%, hepatomegaly in 7.5%, splenomegaly in 6.3%, and cirrhosis in 5.9%. As regards laboratory Results normal alanine aminotransferase was found in 79.8%, normal aspartate aminotransferase in 85.7%, reduced serum albumin in 4.4%, and low platelet count in 9.9%. The majority of patients (91.7%) were hepatitis B envelope antigen negative; 65.9% of patients were positive for HBV on PCR. No significant differences were found between positive HBV-DNA status (by PCR) and negative HBV-DNA status as regards clinical, imaging, and laboratory characteristics of patients. Conclusion Most of the patients had normal liver on ultrasonographic examination and normal liver function tests. No significant difference was found between positive HBV-DNA status (by PCR) and negative HBV-DNA status as regards clinical, imaging, and laboratory characteristics of patients.